Teacher Leadership: Charismatic Characteristics of Sri Lankan School Teachers - Ukwatta Liyanage Thamara Priyanthi Gunasekare (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2019)
This study identifies a number of charismatic leadership characteristics of school teachers in Sri Lanka. Since charisma is an instrumental asset in any work context, leaders’ charismatic characteristics can make extraordinary effects on follower toward mission accomplishment. In the teaching-learning context, teachers are viewed as great leaders that make magnificent transformations in the students. A teacher becomes the leader in the classroom as well and they are playing a significant role to build a culture of learning in the classroom that, finally everyone benefits. Therefore charismatic leadership characteristics in teachers as leaders can make the teaching-learning process more and more effective. This study followed a qualitative research approach, collecting data from interviewing twenty school teachers. It was reported that most of the school teachers are leaders with charismatic characteristics such as mission formulation for the students, unconditioned commitment towards the students’ accomplishments, trust on the students, taking personal risk in directing students, demonstration of unusual behaviors and emotional arousal through attractive communication. The implication of this study is imperative for teacher training and performance appraisals.Keywords: Teacher leadership, charismatic leadership, teaching-learning process, school teachers